Perancangan buku We Love And We Care Pengenalan Hewan dilindungi kepada anak- anak - Dwi Puji Prabowo; Auria F. Yogananti; Erisa Adyati; Shofy Ali Zaky; Ayyub H. B. Nurmana (UNIVERSITAS STEKOM, 2024)
The extermination of animal populations is increasing, due to increased poaching and wildlife trade. This requires learning about caring for animals. Books play a very important role in the world of education, so that the learning process cannot be separated from the learning environment in the form of books. This design aims to produce a book concept about protected animals in Indonesia as an informative medium, providing scientific insight and knowledge about protected animals in Indonesia. The research method used is qualitative as a method for searching for data in the form of verbal data and in visual form. Needs analysis data will be used to obtain a concept for designing the book